Four Galore? The Overlap between Mary Douglas's Grid-Group Typology and Other Highly Cited Social Science Classifications. (September 2020) - Verweij, Marco; Alexandrova, Petya; Jacobsen, Henrik; Béziat, Pauline; Branduse, Diana; Dege, Yonca; Hensing, Jakob; Hollway, James; Kliem, Lea; Ponce, Gabriela; Reichelt, Inga; Wiegmann, Mareile
Recently, neuroscientists have argued that elementary ways of organizing, perceiving, and justifying social relations lurk behind the diversity of social life. In developing grid-group typology, anthropologist Mary Douglas proposed such universal forms. If these are universal, then we could expect other widely cited classifications to overlap with grid-group typology. We tested this expectation by examining to which extent the elements of Douglas's typology overlap with those of 39 highly influential classifications proposed since 1970. We established overlap by calculating the interrater agreement among 11 coders. Fair to good interrater agreement, despite a complex coding exercise and minimal training, suggests that such overlap exists. Nevertheless, limits to our research design call for further studies. These findings should contribute to a rekindling of the question whether universal forms of organizing and perceiving social relations exist and to a further consideration of whether Douglas has managed to uncover these.